2011
DOI: 10.2967/jnumed.111.090175
|View full text |Cite
|
Sign up to set email alerts
|

Association of Heat Production with 18F-FDG Accumulation in Murine Brown Adipose Tissue After Stress

Abstract: Previous studies have demonstrated that cold stress results in increased accumulation of 18FDG in brown adipose tissue (BAT). Although it has been assumed that this effect is associated with increased thermogenesis by BAT, direct measurements of this phenomenon have not been reported. In the current investigation we evaluated the relationship between stimulation of 18FDG accumulation in BAT by three stressors and heat production measured in vivo by thermal imaging. Male SKH-1 hairless mice were subjected to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Reduced UCP1 level in CPEB2‐KO and Ucp1ΔL BAT should cause inefficient non‐shivering thermogenesis and a possible decrease in glucose utilization and metabolism, as indicated by deoxyglucose uptake in UCP1‐KO mice (Inokuma et al , ) and rodents with altered thermogenic activity (Carter et al , ; Tomilov et al , ). Moreover, CPEB2 may regulate translation of other mRNAs besides Ucp1 to affect BAT activity.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced UCP1 level in CPEB2‐KO and Ucp1ΔL BAT should cause inefficient non‐shivering thermogenesis and a possible decrease in glucose utilization and metabolism, as indicated by deoxyglucose uptake in UCP1‐KO mice (Inokuma et al , ) and rodents with altered thermogenic activity (Carter et al , ; Tomilov et al , ). Moreover, CPEB2 may regulate translation of other mRNAs besides Ucp1 to affect BAT activity.…”
Section: Resultsmentioning
confidence: 99%
“…3436 In addition, Virtanen et al reported a 15-fold increase in uptake of FDG into supraclavicular BAT after cold exposure in humans, 5 and Carter et al observed a 15- to 16-fold activation of BAT in mice exposed to cold. 34,35 These data indicate that, irrespective of species and mode of BAT activation, the degree of metabolic activation appears to be of similar magnitude as the blood flow increase of BAT.…”
Section: Discussionmentioning
confidence: 75%
“…This was significantly different from the 0.9 C difference between skin temperature overlying BAT and adjacent skin temperature that was not overlying BAT seen in the control group. 82 Also, there was a strong linear correlation between 18 F-FDG accumulation in BAT and the increase in skin temperature detected by the thermal imaging camera (r 2 D 0.835, P<0 .0001). 82 Several human studies using thermal imaging have been reported.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 81%
“…82 Also, there was a strong linear correlation between 18 F-FDG accumulation in BAT and the increase in skin temperature detected by the thermal imaging camera (r 2 D 0.835, P<0 .0001). 82 Several human studies using thermal imaging have been reported. In one study, volunteers sat in a room (with the temperature maintained at 19-21 C) and were asked to place one hand in water (maintained at a temperature of [19][20] C) for 5 minutes and thermal images were recorded during the 5 minutes immediately preceding the cold stimulus as well as throughout cold stimulation.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 81%
See 1 more Smart Citation